Pengaruh Rasio Berat Zeolit dan Poly Acrilyc Acid (PAA), Waktu Serta Suhu Pada Proses Coating Terhadap Sifat Karakteristik Pupuk Slow Release Fertilizer (SRF) - Dina Adelina (CV. ULIL ALBAB CORP, 2024)
The use of slow-release or controlled-release fertilizers (SRF) is one effective approach to reducing nutrient loss. These fertilizers are designed to release nutrients at a controlled rate and time, aligned with the plant's needs. The nutrient release mechanism can be optimized by manipulating the physical or chemical properties of the fertilizer, involving processes such as diffusion, degradation, and hydrolysis. This study aims to analyze the effects of the mass ratio of zeolite and polyacrylic acid (PAA), as well as the influence of time and temperature during the coating process, on the characteristics of slow-release fertilizers (SRF). The goal is to produce SRF that minimizes negative environmental impacts and reduces costs compared to conventional fertilizers. By adjusting these parameters, it is expected that the resulting SRF will be more effective in gradually supplying nutrients to plants and offer a more economical solution than conventional fertilizers, which tend to deplete quickly or are lost through leaching.